ANALISIS PENGARUH EMOTIONAL QUOTIENT, INTELLIGENCE QUOTIENT DAN SPIRITUAL QUOTIENT TERHADAP KEPUASAN KERJA DAN KINERJA GURU DI SEKOLAH LUAR BIASA NEGERI BATANG - Ary Dwi Anjarini Anjarini (BBM (Buletin Bisnis & Manajemen), 2018)
The main purpose of this study is to strengthen and analyze emotional intelligence, intellectual intelligence and spiritual intelligence to job satisfaction and performance of teachers in the School of Extraordinary Affairs of Batang.    Data were obtained as many as 18 respondents from 18 questionnaires distributed. This research was conducted by using concept. (PLS) for data analysis.   The findings of this study indicate that emotional quotient has no effect on job satisfaction, intelligence quotient has an effect on job satisfaction, spiritual quotient has an effect on job satisfaction, and emotional quotient influence teacher performance, intelligence quotient has no effect on teacher performance, spiritual quotient has no effect on teacher performance , and job satisfaction have a significant effect on teacher performance. Keywords : emotional quotient, intelligence quotient, spiritual quotient, job satisfaction, teacher performance.